Governance Innovation of the Non-Formal Education in Handling the Crisis of Community Learning Services During the Covid-19 Pandemic - Wiwin Herwina; Adang Danial; Cucu Sutianah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The purpose of this study is to reveal the governance of non-formal educational institutions in handling the crisis of community learning services during the Covid-19 pandemic. The method employed in this study was descriptive method with a qualitative approach. The institutions involved in this research were Community Learning Service (PKBM) and Course and Training Institution (LKP) that have been accredited and carried out non-formal education activities during the pandemic situation. The data were collected through in-depth interviews, observation, and documentation with the managers, tutors, and learning residents of the institutions. Data analysis was carried out interactively through several steps: data reduction, data presentation, conclusion drawing/verification. The results of the study showed that in coping the crises, the institutions provided services for community as much as possible while considering the circumstances of social restrictions. The form of governance innovation during the pandemic is strengthening communication between the institutions under the auspices of professional organizations, as well as maximizing the effectiveness of governance innovations on learning, institutional development, adjustment, and strictly implementing the Standard Operating Procedures (SOP) in learning during the Covid-19 pandemic.